Medical malpractice in organ transplantation: public allegations and key legal outcomes - Arvanitis, Panos; Davis, Michel R.; London, Abby; Farmakiotis, Dimitrios (Frontiers in Health Services, 2024)
IntroductionDespite significant advances in surgical techniques and patient outcomes, organ transplantation (OT) remains fraught with legal challenges and ethical dilemmas. This study aims to address the notable gap in literature on malpractice claims specifically related to OT, providing insights into litigation trends, outcomes, and implications for medical practice and patient care.MethodsWe retrospectively queried the Verdictsearch database from 1988 to 2023, and captured malpractice claims involving several organs. Data on demographics, organ types, and litigation outcomes were collected to compare compensation across different categories of malpractice and patient outcomes.ResultsOut of 292 malpractice cases identified, 62 met inclusion criteria, distributed across 19 states with kidney being the most implicated organ (46.8%). Defendants prevailed in 53.2% of cases, while settlements were reached in 29.0%, and plaintiffs won in 16.1% of cases. Surgical errors and complications were the most frequent allegations, followed by medication and treatment errors. The median compensation for deceased plaintiffs was significantly higher (1,300,000) compared to living plaintiffs at litigation initiation (128,000).DiscussionOur study sheds light on the challenges and trends in malpractice litigation within the field of OT. By identifying key areas of concern and the influence of patient outcomes on litigation resolution, this study offers valuable insights for healthcare providers, legal practitioners, and policymakers aimed at enhancing patient safety, reducing litigation risks, and fostering a deeper understanding of the ethical and legal complexities in OT.